Preliminary Development of Vircadia Virtual Reality Platform for Monitoring Water Quality Powered by Solar Panels - Rante, Hestiasari; Achmad, Zacky Maulana; Suaib, Norhaida Mohd; Prasetya, Sonki; Avianto, Tiyo; Hermanu, Adhi Indra; Alfarezi, Fitratama; Wijaya, Ray Yusra (JOIV : International Journal on Informatics Visualization, 2024)
Climate change is a global issue that significantly challenges water resources, especially in regions with limited public awareness about water conservation. It manifests through rising global temperatures, shifting weather patterns, more frequent and intense natural disasters, and instability in water availability. These problems are worsened by low public awareness and the reliance on steam power plants for water pumps. Addressing these challenges requires educational media that raises awareness about the causes and impacts of climate change. This study introduces the early development of a Virtual Reality (VR) platform utilizing Vircadia, focused on creating a 3D world and monitoring water quality with the support of solar power. Vircadia, an open-source platform, offers developers the flexibility to build and host virtual worlds on their servers, providing greater control over the environment, scalability, and customization. With Vircadia, we can rapidly implement a VR platform that integrates custom assets from Blender and personalized avatars from Ready Player Me. Vircadia can seamlessly connect to IoT platforms via weblink, allowing for real-time monitoring of water quality parameters and enabling users to interact directly with and oversee IoT devices within the VR environment. This paper discusses why we chose Ready Player Me and Blender as platforms for building 3D avatars and assets, and Vircadia as the VR Platform. Additionally, it addresses challenges encountered when using Vircadia, such as asset optimization and IoT device integration. Future research will focus on optimizing asset quality, enhancing IoT integration, and implementing carbon emissions monitoring within the VR platform.